Advancing the assessment of pacifier effects with a novel computational method - R. Pereira; J. Romero; A. Norton; J. M. Nóbrega (BMC, 2024)
Abstract Background Numerous studies have demonstrated a high likelihood of malocclusions resulting from non-nutritive sucking. Consequently, quantifying the impact of pacifiers can potentially aid in preventing the development or exacerbation of malocclusions and guide the design of improved performance pacifiers. Methods This work proposes and assesses a computational methodology that can effectively gather crucial information and provide more precise data regarding the consequences of non-nutritive pacifier sucking. The computational framework utilized is based on solids4Foam [1, 2], a collection of numerical solvers developed within the OpenFOAM® computational library [3]. The computational model focuses on the palate of a six-month-old baby and incorporates various components such as palate tissues, pacifier and tongue, and considers the negative intraoral pressure generated and the tongue displacement. Different models were tested, each offering varying levels of detail in representing the palate structure. These models range from a simplified approach, with one tissue, to a more intricate representation, involving up to five different tissues, offering a more comprehensive palate model compared to existing literature. Results The analysis of results involved examining the distribution of stress on the palate surface, as well as the displacement and forces exerted on the dental crowns. By comparing the obtained results, it was possible to evaluate the precision of the approaches previously described in the literature. The findings revealed that the predictions were less accurate when using the simplified model with a single tissue for the palate, which is the most common approach proposed in the literature. In contrast, the results demonstrated that the palate model with the most intricate structure, incorporating five different tissues, yielded distinct outcomes compared to all other combinations. Conclusions The computational methodology proposed, employing the most detailed palate model, has demonstrated its effectiveness and necessity in obtaining accurate data on the impact of non-nutritive sucking habits, which are recognized as a primary contributor to the development of dental malocclusions. In the future, this approach could be extended to conduct similar studies encompassing diverse pacifier designs, sizes, and age groups. This would foster the design of innovative pacifiers that mitigate the adverse effects of non-nutritive sucking on orofacial structures.